2021
DOI: 10.19184/jkrn.v2i2.25410
|View full text |Cite
|
Sign up to set email alerts
|

Pemanfaatan Metode Penyuluhan Pertanian Oleh Petani Cabai Merah

Abstract: The contribution of extension and the use of innovation in agriculture, especially red chili, is needed by farmers to improve agricultural development. Agricultural extension to the red chili farming community in Tamansari Village, Wuluhan District, Jember Regency, East Java, to improve farmers' knowledge and skills regarding an innovation and help increase production. The application of extension methods to red chili farmers has different responses in accepting an innovation or technology. The purpose of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 6 publications
0
7
0
2
Order By: Relevance
“…However, it demands thorough preparation in terms of funding, materials, and farmer readiness. It is the same with Mardikanto & Pertiwi (2019) and Ramadhana & Subekti (2021) finding that the demonstration method in agricultural extension is effective in increasing farmer knowledge, but it will increase the cost is increase too about serving the program. The lecture method is commonly used, involving theoretical information about "Jajar Legowo."…”
Section: Extension Supportmentioning
confidence: 83%
See 1 more Smart Citation
“…However, it demands thorough preparation in terms of funding, materials, and farmer readiness. It is the same with Mardikanto & Pertiwi (2019) and Ramadhana & Subekti (2021) finding that the demonstration method in agricultural extension is effective in increasing farmer knowledge, but it will increase the cost is increase too about serving the program. The lecture method is commonly used, involving theoretical information about "Jajar Legowo."…”
Section: Extension Supportmentioning
confidence: 83%
“…Practical demonstrations effectively convey the Jajar Legowo system but are infrequently used due to resource demands. Mardikanto & Pertiwi (2019) and Ramadhana & Subekti (2021) highlight the effectiveness of demonstrations but note limitations in cost and time. Extension workers involve farmer groups and field block leaders in demonstrations, followed by reinforcement through lectures and discussions.…”
Section: The Relationship Between Extension Support and The Implement...mentioning
confidence: 99%
“…The position of farmers in downstream innovative technology acts as a recipient and implementer of innovative technology, according to [40; 41] The dissemination of information technology at the regional level occurs through various channels (multi-channel), as shown in Figure 6. Technology information received by farmers is not only from sources directly related to technology preparation institutions but also from cyberspace media [42] ; [41]; [40]; [43] Facts in the field, farmers who meet their seed needs by ordering through the market place.…”
Section: Results and Discussion A Characteristics Of The Respondent F...mentioning
confidence: 99%
“…This can be seen from a number of questions submitted to socialization participants (specifically questions numbers 4 and 6) showing that 65.71-74.28% of the total socialization participants gave a good response at the end of the socialization activity. Ramadhana & Subekti (2021) reported that the group method was the most effective activity in counseling because farmers could hold discussions, demonstrate tools and consult with extension workers in Tamansari Village, Wuluhan District, Jember Regency, East Java. Dwiyanti (2016) also reported that the process of implementing the extension method using the demonstration method was an effective method used in counseling on shallot farming in Pucak Village, Tompobulu District, Maros Regen…”
Section: Demonstration Activitiesmentioning
confidence: 99%